Beyond Technocratic Competence: A Psychometric Validation of a Values-Embedded Teacher Assessment Model in Indonesian Islamic Schools - Hindun Chotijah; Suparman; Dian Artha Kusumaningtyas (Jurnal Pendidikan Agama Islam, 2025)
Purpose – Teacher competency assessments often emphasize technical performance and administrative compliance while paying limited attention to ethical and religious value frameworks that shape professional identity in faith-based schools. In Muhammadiyah education, Al Islam and Kemuhammadiyahan (AIK), integrating Islamic teachings and institutional values, guides teachers’ professional conduct and educational practice. However, these values have rarely been operationalized within empirically validated teacher competency frameworks. This study develops and validates a teacher competency assessment model integrating AIK values into professional standards for Muhammadiyah elementary school teachers. Design/methods/approach – This research employs a research and development framework with a sequential mixed methods design, combining qualitative exploration, expert validation, and quantitative testing involving 343 teachers. AIK values were translated into observable behavioral indicators across four competency domains: pedagogical, professional, social, and personality. Psychometric evaluation assessed content validity, internal consistency reliability, and construct validity using factor-based model testing. Findings – The final instrument comprises 30 items representing the four competency domains integrated with AIK values. Results demonstrate strong content validity and high reliability, with composite reliability ranging from 0,787 to 0,893. Construct validation shows acceptable model fit (RMSEA = 0,074; SRMR = 0,073), supporting the structural coherence of the AIK integrated competency model. Research implications/limitations – This study offers an empirically grounded framework linking Islamic educational values with psychometric assessment, although broader cross-regional validation is recommended. Originality/value – This research bridges Islamic educational philosophy with contemporary psychometric practice and provides a model for value-embedded competency assessment applicable to other faith-based or culturally specific educational contexts.